TEST-TAKING DIFFICULTIES IN ENGLISHSCORE READING ASSESSMENT: INSIGHTS FROM LEARNER EXPERIENCES - Arisandi, Vidya; Yulianti, Hilda tri; Prihamdani, Depi; Juanda, Juanda; Mulya, Pasya Wijaksono (Universitas PGRI Sumatera Barat, 2025)
Reading comprehension is a crucial skill for English as a Foreign Language (EFL) learners, particularly in the context of standardized language proficiency assessments. This study examines the test-taking challenges encountered by 30 non-English major university students during their initial experience with the EnglishScore reading test, an adaptive, mobile-based English assessment developed by the British Council. Employing a qualitative descriptive research design, the study collected data through open-ended reflections and analyzed them using a thematic analysis approach. Researchers identified five main categories of difficulty: (1) time pressure, (2) vocabulary limitation, (3) text complexity, (4) translation and interpretation challenges, and (5) test unfamiliarity and strategic disorientation. The findings indicate that learners experienced difficulties that were multidimensional and mutually reinforcing, as linguistic, cognitive, and procedural gaps converged to impede their performance. Limited vocabulary knowledge and dependence on literal translation strategies negatively impacted comprehension. Additionally, stringent time constraints and unfamiliar digital formats exacerbated anxiety and cognitive overload. These findings emphasize the need for comprehensive reading instruction that encompasses vocabulary development, strategic reading skills, and practice with simulated testing—particularly for EFL learners who are unfamiliar with high-stakes, time-restricted digital assessments. This study contributes to the growing body of literature on mobile-based reading assessment and highlights important implications for curriculum designers, educators, and test developers.